The development of managerial mechanisms to ensure a technological breakthrough in the Russian economy - O. I. Dontsova; N. M. Abdikeev; Yu. S. Bogachev (Управленческие науки, 2020)
The paper is devoted to improving managerial tools to ensure the effective implementation of technological breakthrough in the Russian economy. Solving the tasks of socio-economic development of the country, improving the quality of life of the population, ensuring its geopolitical position is impossible without accelerated economic growth. To ensure it, a technological breakthrough is needed in the Russian economy. In order to create appropriate conditions, new management mechanisms are needed in high-tech corporations. The methodological base of the study is based on the provisions of the theory of corporate governance, system, factor, functional and statistical analysis. The paper analyzes the experience of organizations of accelerated technological development and concludes on the effective structure of the managerial apparatus, which coordinates and monitors the activities of corporations. The main directions of state policy to ensure economic growth are identified, a factor analysis of its effectiveness and mechanisms for the formation of the conditions for the implementation of technological breakthrough are carried out. The domestic scientific potential of providing a technological breakthrough in the Russian economy is shown, the effectiveness of mechanisms for converting scientific achievements into breakthrough technologies is considered. The analysis results carried out in the work indicate the absence of a system of concentration of scientific potential for the creation of high-tech innovations. The structure of the scientific and technical platform for generating knowledge and its transformation into competitive technologies in priority sectors of the real sector of the economy is proposed, its organizational form is determined. The work results can be used in solving strategic problems of modernization of high-tech manufacturing industries.